Liver function test as a marker for acute appendicitis - Yadav, S; Chandra, K (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: Acute appendicitis is one of the commonest surgical emergencies of the abdomen worldwide. Even with the availability of current imaging investigation like USG , CT scan and MRI, the diagnosis is still a problem. Delay in diagnosis increases mortality and morbidity. Liver function test is one of the biochemical parameters being assessed as a marker of acute appendicitis and may also predict the severity of the inflammation. However the available literature is limited and views are conflicting. In this study, it is proposed to access the validity of using liver function test to predict the appendicitis and its severity.Material and Methods: This is a prospective study of 80 cases of operated patients of acute appendicitis in Universal College Of Medical Sciences, Bhairahawa, Nepal during the period from 6th May 2013 to 6th July 2014. Data were collected from the patient by their clinical history, examination and investigations, Liver function test and ultrasound. Post operative follow up was done to note for complications and histopathology findings. Data collection was compiled in a systemic way in preformed proforma and analyzed.Results: Out of 80 patients, 44(55%) were male and 36(45%) were female. Total serum bilirubin was elevated in 29 (36.25%) of the patients. Rise in serum bilirubin was mixed type with direct bilirubin Predominance. In Liver enzymes ALT, AST, ALP were raised in 32.5%, 28.75% and 82.5% respectively. Hyperbilirubinemia has the specificity (80 %) sensitivity (37.33%) with good positive predictive value of 96.55%. Similarly sensitivity and specificity of direct bilirubin (90.67%, 20.00%), Indirect bilirubin (16.00%, 80%), AST/SGOT (30.67%, 100%), ALT/SGPT (34.67%, 100%) ALP (84.00%, 40%) respectively. The positive predictive value for direct bilirubin, indirect bilirubin, AST/SGOT, ALT/SGPT and ALP are 94.44%,92.31%,100%,100% and 95.45% respectively.Conclusion: Liver function test is a marker for acute appendicitis and its complication with a good positive predictive value. Liver function test should be used together with clinical examination and other laboratory investigations in the assessment of patients with suspected acute Appendicitis.Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (1):31-36